A Navigating Chronic Conditions in Primary Care : A Case of Recurrent Tinea Corporis and Prediabetes - Arifin, Samsul; Nauli Purba, Edelen; Brakumara , Aditya (Jurnal Ilmu Kedokteran Keluarga, 2025)
Chronic conditions like tinea corporis and prediabetes significantly impact patient quality of life and present multifaceted challenges in primary care. This case report highlights the complex interplay between lifestyle factors, personal hygiene, and the recurrence of dermatological and metabolic issues within a family medicine context. We present a 39-year-old female with a two-year history of recurrent, intensely pruritic tinea corporis, currently manifesting on her right crus. Concurrently, she was diagnosed with prediabetes. Contributing factors included a sedentary lifestyle, poor dietary habits marked by frequent sweet consumption, and suboptimal personal hygiene, such as infrequent bathing and inadequate skin drying. Her mother also had a history of Type 2 Diabetes Mellitus. Discussion : This case underscores the crucial role of family medicine in addressing co-morbidities and lifestyle-related health issues. The patient's recurrent fungal infection was exacerbated by poor hygiene and a constantly moist skin environment due to sweating and inadequate drying. Her prediabetes, linked to obesity and a family history of diabetes, was further compounded by a sedentary lifestyle and poor dietary choices. Effective management necessitates a holistic, family-centered approach, integrating education on hygiene, dietary modifications, increased physical activity, and consistent adherence to medication, rather than solely focusing on symptomatic relief. Managing chronic, lifestyle-influenced conditions like recurrent tinea corporis and prediabetes requires comprehensive primary care interventions. A holistic approach that educates patients on self-care, promotes healthy lifestyle changes, and considers family health dynamics is paramount for achieving sustained improvement and preventing disease progression.